EFEKTIVITAS PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DALAM RANGKA PERCEPATAN PENDAFTARAN TANAH PADA KANTOR BADAN PERTANAHAN NASIONAL KOTA MAKASSAR - Jamaluddin Jamaluddin; Nursadrina Nursadrina; Muh. Nasrullah Muh. Nasrullah; Muh. Darwis; Rudi Salam (Jurnal Pallangga Praja (JPP), 2021)
This study aims to determine the effectiveness of the complete systematic land registration program(PTSL) in the context of accelerating land registration at the Makassar City National Land Agencyoffice. To find out these objectives, the researchers used a qualitative research approach witha descriptive type of research. The informants in this study were 7 people using data collectiontechniques that were carried out through observation, interviews, and documentation. From thoseobtained from the research results, it was processed using data analysis techniques consisting ofdata reduction, data presentation, and conclusions. The results showed that the Effectiveness ofthe Complete Systematic Land Registration Program (PTSL) in the Context of Accelerating LandRegistration seen from the indicators of the accuracy of program targets was good, based on programsocialization it was good, as well as the achievement of program objectives was good, and programmonitoring was good in the effectiveness of the Registration program. Complete Systematic Soil.